Altered Properties of Endothelial Cells and Mesenchymal Stem Cells Underlying the Development of Scleroderma‐like Vasculopathy in KLF5+/−;Fli‐1+/− Mice. Issue 12 (30th October 2020) - Nakamura, Kouki; Taniguchi, Takashi; Hirabayashi, Megumi; Yamashita, Takashi; Saigusa, Ryosuke; Miura, Shunsuke; Takahashi, Takehiro; Toyama, Tetsuo; Ichimura, Yohei; Yoshizaki, Ayumi; Trojanowska, Maria; Fujiu, Katsuhito; et al.
Abstract : Objective: In prevous studies, we established a new animal model, KLF5 +/− ;Fli‐1 +/− mice, in which fundamental pathologic features of systemic sclerosis (SSc) are broadly recapitulated. SSc vasculopathy is believed to occur as a result of impaired vascular remodeling, but its detailed mechanism of action remains unknown. To address this, the present study investigated the properties of dermal microvascular endothelial cells (DMECs), bone marrow–derived endothelial progenitor cells (BM‐EPCs), and bone marrow–derived mesenchymal stem cells (BM‐MSCs), a precursor of pericytes, in KLF5 +/− ;Fli‐1 +/− mice. Methods: Neovascularization and angiogenesis were assessed in KLF5 +/− ;Fli‐1 +/− mice by in vivo Matrigel plug assay and in vitro tube formation assay, respectively. The properties of mouse BM‐EPCs and BM‐MSCs were assessed with in vitro studies. Dermal vasculature was visualized in vivo by injecting the mice with fluorescein isothiocyanate–conjugated dextran. Results: Neovascularization was diminished in skin‐embedded Matrigel plugs from KLF5 +/− ;Fli‐1 +/− mice. DMECs from KLF5 +/− ;Fli‐1 +/− mice showed defective tubulogenic activity, decreased expression of VE‐cadherin and CD31, and an imbalance in the expression of Notch 1 / Dll4, suggesting that angiogenesis and anastomosis are disturbed. KLF5 +/− ;Fli‐1 +/− mouse BM‐MSCs exhibited enhanced proliferation and migration and increased collagen production following stimulation with transforming growth factor β1, indicating that these cells differentiate preferentially into myofibroblasts rather than pericytes. KLF5 +/− ;Fli‐1 +/− mouse BM‐EPCs displayed a transition toward mesenchymal cells, suggesting that vasculogenesis is impaired. Wound healing was delayed in KLF5 +/− ;Fli‐1 +/− mice (mean ± SD healing time 15.67 ± 0.82 days versus 13.50 ± 0.84 days; P = 0.0017), and the vascular network was poorly developed in wound scar tissue. Conclusion: The characteristics observed in the KLF5 +/− ;Fli‐1 +/− mouse model — specifically, impaired neovascularization and vascular maturation — are similar to those observed in human SSc, and could be at least partially attributable to the induction of SSc‐like properties in DMECs, BM‐EPCs, and BM‐MSCs. These findings indicate the critical contribution of Klf5 and Fli1 deficiency in vascular cells and related cell precursors to the development of SSc vasculopathy.